Filter Design on Discrete-Time Neutral System Using Guaranteed Cost Method - Erwin Susanto; Ig. Prasetya Dwi Wibawa; Junartho Halomoan (Indonesian Journal of Physics, 2015)
This paper will discuss about our study in filter design on discrete-time neutral system using guaranteed cost method. This design filter method yields a robust filter and the derivation of its equation can be obtained by using LMI (linear matrix inequalities).